Textbooks based on local wisdom to improve reading and writing skills of elementary school students - Alfi Laila; C. Asri Budiningsih; Kastam Syamsi (Institute of Advanced Engineering and Science, 2021)
Many elementary students still find it difficult to understand the literature content used and it automatically affects their reading and writing skills. However, the adjustment of literature with local wisdom-based content needs to be considered as a supporting tool. This study aimed to improve reading and writing skills using textbook based on local wisdom. The sample was grade 4 of elementary school students who selected using purposive random sampling. This research used a nonequivalent control group design through the experiment and control classes. Data were collected through writing and reading skills test of 32 students in each class and analyzed using N-gain to describe the treatment effect. The results showed that textbooks based on local wisdom were more effective than teaching materials that were not integrated by local wisdom at improving students' reading and writing skills. In the future, this study is a reference for teachers to apply local wisdom to other learning themes.